The rise and spread of mcr plasmid-mediated polymyxin resistance. (4th March 2019) - Nang, Sue C.; Li, Jian; Velkov, Tony
Abstract: Polymyxins are important lipopeptide antibiotics that serve as the last-line defense against multidrug-resistant (MDR) Gram-negative bacterial infections. Worryingly, the clinical utility of polymyxins is currently facing a serious threat with the global dissemination of mcr, plasmid-mediated polymyxin resistance. The first plasmid-mediated polymyxin resistance gene, termed as mcr-1 was identified in China in November 2015. Following its discovery, isolates carrying mcr, mainly mcr-1 and less commonly mcr-2 to -7, have been reported across Asia, Africa, Europe, North America, South America and Oceania. This review covers the epidemiological, microbiological and genomics aspects of this emerging threat to global human health. The mcr has been identified in various species of Gram-negative bacteria including Escherichia coli, Klebsiella pneumoniae, Klebsiella oxytoca, Salmonella enterica, Cronobacter sakazakii, Kluyvera ascorbata, Shigella sonnei, Citrobacter freundii, Citrobacter braakii, Raoultella ornithinolytica, Proteus mirabilis, Aeromonas, Moraxella and Enterobacter species from animal, meat, food product, environment and human sources. More alarmingly is the detection of mcr in extended-spectrum-β-lactamases- and carbapenemases-producing bacteria. The mcr can be carried by different plasmids, demonstrating the high diversity of mcr plasmid reservoirs. Our review analyses the current knowledge on the emergence of mcr -mediated polymyxin resistance.